Analog circuit and system design : a tutorial guide to applications and solutions - Dobkin, Bob; Williams, Jim, 1948-2011 (Elsevier/Newnes, 2011)
"Covers the fundamentals of linear/analog circuit and system design to guide engineers with their design challenges -- Based on the Application Notes of Linear Technology, the foremost designer of high performance analog products, readers will gain practical insights into design techniques and practice -- Broad range of topics, including power management tutorials, switching regulator design, linear regulator design, data conversion, signal conditioning, and high frequency/RF design. -- Contributors include the leading lights in analog design, Robert Dobkin, Jim Williams and Carl Nelson, among others. ... Analog circuit and system design today is more essential than ever before. With the growth of digital systems, wireless communications, complex industrial and automotive systems, designers are challenged to develop sophisticated analog solutions. This comprehensive source book of circuit design solutions will aid systems designers with elegant and practical design techniques that focus on common circuit design challenges. The book's in-depth application examples provide insight into circuit design and application solutions that you can apply in today's demanding designs."--Provided by publisher